2011
DOI: 10.1007/s00595-010-4421-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngolaryngoesophagectomy in a patient with an aberrant right subclavian artery: Report of a case

Abstract: We report a case of carcinoma of the hypopharynx and cervical esophagus in a patient with an aberrant right subclavian artery. Barium esophagography, endoscopy, and computed tomography showed a resectable tumor in the hypopharynx and cervical esophagus, coexistent with an aberrant right subclavian artery. We performed pharyngolaryngoesophagectomy with bilateral neck dissection and gastric pull-up through cervical, right thoracic, and abdominal incisions. We also partially resected the aberrant right subclavian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…With a total of 39 included studies, for the 27 studies that had an N > 1, [24–50] the following data were collected: the total number of subjects included in the studies was 41,178 with an average ratio of 1.525:1 regarding the sex of the sample; 12 studies did not indicate the sex of their sample [25,27,31,34,35,37,38,45,47–50] ; one study by Yusuf et al [32] only indicates the sex of the sample that did present the anatomical variant and consisted of 10 men and 17 women, respectively; and, finally, 14 studies [24,26,28–30,33,39–44,46] show that the cumulative data for males was 2964/5393, which is equivalent to 54.9%, and cumulative data for females was 2429/5393, which is equivalent to 45.1%. Finally, regarding the geographical distribution of the included studies, [24–50,53–64] in 13 studies, the sample was European, which is equivalent to 33.3% of the included studies; in 12 studies, the sample was from North America, which is equivalent to 30.8% of the included studies; and, finally, 14 studies had a sample from Asia, which is equivalent to 35.9% of the studies included in this review (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…With a total of 39 included studies, for the 27 studies that had an N > 1, [24–50] the following data were collected: the total number of subjects included in the studies was 41,178 with an average ratio of 1.525:1 regarding the sex of the sample; 12 studies did not indicate the sex of their sample [25,27,31,34,35,37,38,45,47–50] ; one study by Yusuf et al [32] only indicates the sex of the sample that did present the anatomical variant and consisted of 10 men and 17 women, respectively; and, finally, 14 studies [24,26,28–30,33,39–44,46] show that the cumulative data for males was 2964/5393, which is equivalent to 54.9%, and cumulative data for females was 2429/5393, which is equivalent to 45.1%. Finally, regarding the geographical distribution of the included studies, [24–50,53–64] in 13 studies, the sample was European, which is equivalent to 33.3% of the included studies; in 12 studies, the sample was from North America, which is equivalent to 30.8% of the included studies; and, finally, 14 studies had a sample from Asia, which is equivalent to 35.9% of the studies included in this review (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…And in the third type, the artery runs anterior to the trachea. [66] For the included studies that could be classified according to their origin with respect to what was proposed by Williams et al, [66] 7 studies [32,54–56,59,63,64] reported the ARSA variant, showing the characteristics according to origin in 6 studies, [32,55,56,59,63,65] the variant is classified as type I in its origin, while 2 studies [54,55] showed that ARSA was classified as a different type of variant according to its origin and the classification. While 11 studies [24,29,32,55–57,59,61–64] in their description classified the route as type I, for the classification of type II, route 2 studies [24,59] presented this pattern; finally, for the type III route classification, no studies were presented (Tables 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different approaches include hybrid vascular and endovascular repair [4], and direct surgical repair. The latter can be obtained through a variety of corridors including extrathoracic [[5], [6], [7], [8]], or transthoracic (thoracotomy) [9,10], all accompanied with certain morbidities and mortalities.…”
Section: Introductionmentioning
confidence: 99%